Digital Marketing Training For Home Businesses In Bodag Village, Ngadirojo District, Pacitan Regency - Hiryanto, Hiryanto; Slamet Setiana, Dafid; Desi Aryani, Neng (Universitas Negeri Padang, 2024)
This Community Service Activity for Real Work Lectures (PkM KKN) aims to provide knowledge and skills to the community, especially those who have businesses at Real Work Lecture locations, so they can market their businesses through various digital platforms such as Shoppi, Lazada, and other social media. The approach used in implementing this KKN PkM activity is to first make preparations, which consist of registering data on potential participants and their businesses, contacting village officials and preparing training places, contacting resource persons, then carrying out KKN PkM activities on a previously determined day and ending with evaluation. The Real Work Lecture activity, which is part of Community Empowerment or Community Service, was carried out for 2.5 months, in this regard, digital marketing training was carried out for home businesses at the KKN location on Saturday, October 28 2023, which presented speakers from business actors who use digital marketing, this activity was attended by a target group of 27 people who have various home businesses, such as a small specialty food industry from the village, so by participating in this activity it is hoped that they can market their business more widely and their income will increase. Apart from delivering material and practice, PkM activities also include mentoring provided by KKN participants so that they can truly market their businesses. After completing the activity, the participants were evaluated through observation and interviews with the results, the majority stated that this activity was very useful and felt happy, with the hope that it could be applied to increase income, apart from that they also gained new knowledge and skills, the hope was that there would be mentoring and other training, as well as understanding how to market your business products via cellphone.